STRATEGIES FOR ENHANCING PEDAGOGICAL COMPETENCE IN THE MODERN EDUCATION SYSTEM (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the essence and significance of pedagogical competence in the modern education system, as well as effective ways of developing and enhancing it in professional teaching practice. The study also examines the application of innovative technologies in the educational process, continuous professional development, the formation of digital competencies, and the improvement of teachers’ professional capacity through a competency-based approach. Furthermore, the theoretical and practical aspects of pedagogical competence development are explored, and a set of recommendations and proposals for its improvement in modern educational institutions is presented.